"But Do the Lord Care?". Issue 4 (1st July 2014) - GRIMES, KATIE
Abstract The slain rapper Tupac Shakur contributes indispensably to two contemporary theologies centered around the crucified people, the theological aesthetics of liberation presented by Roberto Goizueta and the theology of the lynching tree articulated by James Cone. Placing the pioneering work of Goizueta and Cone in conversation with existing scholarship on the theological importance of Shakur's music, I argue that Tupac crafts a theological aesthetics of liberation aimed at illuminating the injustice and Christological implications of the hypersegregated ghetto and the black mass prison